Introducing the non-invasive prenatal testing for detection of Down syndrome in China: a cost-effectiveness analysis. Issue 7 (6th July 2021) - Shang, Wenru; Wan, Yang; Chen, Jianan; Du, Yanqiu; Huang, Jiayan
Abstract : Objective: This study aimed to compare the health economic value of a non-invasive prenatal testing (NIPT) strategy against a second-trimester triple screening (STS) strategy for the detection of Down syndrome based on real-world data from China. Design: A decision-analytical model was developed to compare the cost-effectiveness of five strategies from a societal perspective. Cost and probability input data were obtained from the real-world surveys and published sources. Setting: China. Participants: Women with a singleton pregnancy. Interventions: The five strategies for screening were: (A) maternal age with STS (no NIPT); (B) STS plus NIPT screening; (C) age-STS plus NIPT screening (the currently referral strategy in China); (D) maternal age with NIPT screening and (E) universal NIPT screening. Main outcome measures: Incremental cost-effectiveness ratios (ICERs) per additional Down syndrome case terminated, univariate and probabilistic sensitivity analysis and cost-effectiveness acceptability curves were obtained. Results: Strategy A detected the least number of Down syndrome cases. Compared with the cheapest Strategy B, Strategy D had the lowest ICER (incremental cost, US$98 944.85 per additional Down syndrome case detected). Strategy D had the highest probability of being cost-effective at the willingness-to-pay level between US$110 000.00 and US$535 000.00 per additional Down syndrome case averted. Strategy E would not be cost-effective unless the unit cost of the NIPT could be decreased to US$60.50. Conclusion: Introducing NIPT screening strategies was beneficial over the use of STS strategy alone. Evaluating maternal age in combination with the NIPT screening strategy performs better than China's currently referral strategy in terms of cost-effectiveness and safety. Lowering the price of NIPT and optimising payment methods are effective measures to promote universal NIPT strategies in China.